HUBUNGAN HUBUNGAN TINGKAT PENGETAHUAN DENGAN KECEMASAN PADA PASIEN YANG AKAN DILAKUKAN TINDAKAN ENDOSKOPI DI UNIT ENDOSKOPI RSUD ARIFIN ACHMAD PROVINSI RIAU - Ahmad Redho; Jannaim; Rahmaniza; Hidayat Makruf (Jurnal Ilmu Keperawatan, 2022)
Endoscope is a tool that is used to examine internal organs of the body, especially the gastrointestinal tract visually by aiming through the instrument by looking through the monitor screen, and can clearly see any abnormalities of the organ being examined. Anxiety in endoscopy is triggered by a procedure such as fear. , pain and discomfort. inadequate information and not knowing what to expect during the process. Reducing anxiety requires knowledge. Knowledge is an important domain in the formation of open behavior or open behavior. The sample of this study amounted to 80 people. The sampling method used accidental sampling technique by taking into account the inclusion criteria. The analytical method used is univariate and bivariate analysis. The results of the Chi-Square static test show that there is a relationship between knowledge and anxiety of patients who will undergo endoscopy where the p value <0.05. The results of this study are expected to assist nurses in determining appropriate nursing interventions to reduce anxiety arising from endoscopy.